Assessing groundwater storage and groundwater level fluctuations in the area of Fort Collins, Colorado - Almahawis, Mohammed, author; Bailey, Ryan T., advisor; Scalia, Joseph, IV, committee member; Sanford, William E., committee member (Colorado State University. Libraries, 2018)
Although groundwater is the main water supply for many municipalities worldwide, shallow groundwater can adversely affect urban areas via soil waterlogging and impacts on building foundations and general city infrastructure. A quantitative assessment of groundwater levels and temporal fluctuations is needed to determine the extent to which groundwater should be managed to prevent these adverse conditions. This thesis assesses past and current groundwater storage and groundwater levels in the city limits of Fort Collins, Colorado, a moderate-sized municipality situated in the Front Range of the Rocky Mountains in the western United States. Currently, Fort Collins uses only surface water for its water supply, with the underlying unconfined alluvial aquifer mostly unused and close to ground surface. The assessment includes developing quantitative groundwater maps (depth to water table, water table elevation, and saturated thickness), estimating groundwater recharge and change in storage during large rainfall events, and defining areas with risk of high groundwater level. Observed depth to water table data from various sources was collected for two-time frames (1959-1979 and 2000-2017). The Stanford Geostatistical Modeling Software (SGeMS) was used to interpolate soil and groundwater data, and a Geographic Information System (GIS) was used to develop maps, estimate the storage, and define areas with potential risk of high groundwater level. Also, the Natural Resources Conservation Service's (NRCS) curve number method was performed to quantify recharge from high-intensity rainfall events. NRCS curve number method is a widely used method to quantify the amount of runoff due to a rainfall event. Comparing results from the two-time frames, the depth to water table in the study area has increased slightly (0.32 m) with a 3.9 m current average depth to the water table. Storage has decreased from 126.8 million m3 to 122 million m3, largely due to pumping groundwater for irrigation in the northeast area of the city limits. Approximately 10% of parcels in the Fort Collins area are at risk of high groundwater level. Most parcels along the Cache La Poudre River have problems with high groundwater level. The amount of recharge to the shallow aquifer in the Fort Collins area due to 10 and 100-year return-period storms is approximately equal to 1.9 million m3 and 3.3 million m3, respectively. Also, the percentage of the parcels at risk of high groundwater table will increase to 11% and 12%, respectively. The resulting groundwater maps, and the response of water table to rainfall events, can assist city water managers with identifying areas of potential risk to shallow groundwater conditions. In addition, the methods applied in this thesis can be used for other urban areas containing a shallow alluvial aquifer.